Konsep Kebebasan dalam Pemikiran John Stuart Mill dan Muhammad Abduh: Studi Komparatif Filsafat Barat dan Islam - Januar, Muji Kaliya; Muhlas, Muhlas; Hakim, Maman Lukmanul; Negara, Muhammad Adress Prawira (Jurnal Riset Agama, 2025)
This study aims to analyze and compare the concept of freedom in the thoughts of John Stuart Mill and Muhammad Abduh as representations of Western and Islamic philosophical traditions. The background of this research lies in the complexity of interpreting freedom within different civilizational contexts, which has implications for both theoretical and practical dimensions of life. The study employs a qualitative method with a philosophical comparative approach based on library research. Primary data were obtained from the works of Mill and Abduh, supported by secondary sources such as books and scholarly articles. The findings reveal that Mill defines freedom as an individual right limited by the harm principle, aiming to create the greatest happiness for society. In contrast, Abduh places freedom within the Islamic theological framework, viewing it as a divine gift bound by moral and sharia principles. Despite fundamental differences in the sources and limitations of freedom, both thinkers agree that freedom of thought is a crucial instrument for civilizational progress. The conclusion of this study emphasizes the philosophical differences between Mill and Abduh, reflecting their respective epistemological contexts, while also highlighting opportunities for cross tradition dialogue. Recommendations from this research include developing educational policies that integrate the values of freedom and social responsibility to build a harmonious and progressive society.